1995
DOI: 10.1002/ijc.2910600113
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of human keratinocytes is characterized by quantitative and qualitative alterations of the T‐16 antigen (Trop‐2, MOv‐16)

Abstract: The regulation of synthesis and post-translational processing of the T-16 antigen, a human cell-surface glycoprotein of 50 to 60 kDa, was investigated in normal and transformed human keratinocytes in vitro. Normal keratinocytes of interfollicular and follicular origin were compared with squamous-cell-carcinoma lines, spontaneously immortalized keratinocytes, and SV-40 transformed keratinocytes. FACS analysis and radio-immunoprecipitation showed that the synthesis and expression of T-16 was 3- to 4-fold higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The pattern of deglycosylation achieved with the three enzymes was similar in all the three cell lines studied. The higher molecular weight of gp130 in SK-CO-2 cells may result from differential glycosylation (as has been described for other surface glycoproteins in some tumor cells (Schö n and Orfanos, 1995)). When the L101 mAb was used to detect the gp130 deglycosylation products, the same pattern as detected with the BT14 mAb was seen (not shown).…”
Section: Resultsmentioning
confidence: 75%
“…The pattern of deglycosylation achieved with the three enzymes was similar in all the three cell lines studied. The higher molecular weight of gp130 in SK-CO-2 cells may result from differential glycosylation (as has been described for other surface glycoproteins in some tumor cells (Schö n and Orfanos, 1995)). When the L101 mAb was used to detect the gp130 deglycosylation products, the same pattern as detected with the BT14 mAb was seen (not shown).…”
Section: Resultsmentioning
confidence: 75%
“…Based on this assumption, EpCAM with its restricted spatial and temporal expression is relevant to morphogenesis. Further support for the role of EpCAM in morphogenesis comes from mechanistic studies showing that EpCAM expression is indeed associated with cell proliferation and differentiation during organogenesis (7)(8)(9)11,24).…”
Section: Discussionmentioning
confidence: 99%
“…Reversely, EpCAM might be an active regulator of cell differentiation. Circumstantial evidence for such a role comes from ectopic overexpression of EpCAM, which induces redifferentiation in terminally differentiated cells, such as keratynocytes (7,8). However, the debate on EpCAM as active regulator of differentiation or as a "passive" player in this process is still wide open.…”
Section: Epcam In Early Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…A defect in receptor glycosylation is supported by a reported defect in N-linked glycosylation in HaCat cells as well as other transformed keratinocyte cell lines. 49 However, PGE 2coupled receptors may exhibit other posttranslational modifications including isoprenylation and phosphorylation. 48,50 We have previously demonstrated that EP 2 receptor activation stimulates growth in PHKs.…”
Section: Discussionmentioning
confidence: 99%